Un rilievo da Roma agli Uffizi.: Vicende collezionistiche e analisi archeologica - D'Andrea, Francesca (Römische Mitteilungen, 2021)
The object of this paper is a Roman relief discovered in Rome and now exhibited at the Galleria degli Uffizi in Florence. Although the relief has been known since the Renaissance, its provenance, chronology and interpretation are still a matter of debate. The first part of this study retraces the modern history of the relief, from the Villa Medici Collection to the Uffizi, through the examination of the antiquarian, iconographic and archival sources. Then attention is devoted to the archaeological study. The scene depicts the sacrifice of a bull, performed by the victimarii, in the presence of a togatus, two children holding a shield, a personification and, significantly, a palm tree. The paper offers a stylistic and iconographic analysis and an explanation of the relief, hitherto poorly investigated.